2020
DOI: 10.1109/access.2020.3040546
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Reconstruction Accuracy of Marine Gravity Anomaly Encrypted Reference Map Using the New Mean Sea Surface 3-D Correction Method

Abstract: The reconstruction methods of marine gravity anomaly encrypted reference map are studied in this study, which can improve the accuracy of underwater gravity matching navigation. Firstly, the mean sea surface as the third dimension component was introduced into the semivariance function of the traditional Kriging two-dimensional (2-D) interpolation method for the first time. After that, a new mean sea surface three-dimensional (3-D) correction method was proposed in order to improve the spatial resolution of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Related research showed that there are implications for satellite altimeter inversion of the marine gravity field in some areas with significant variation in the seafloor topography [22]. In addition to the density and reliability of the satellite altimeter data, topographical factors may also lead to inconsistency in the trend of the distribution of values during the interpolation process [32]. In two figures, there are significant differences between the marine…”
Section: Verification From Coastal Gravity Field Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Related research showed that there are implications for satellite altimeter inversion of the marine gravity field in some areas with significant variation in the seafloor topography [22]. In addition to the density and reliability of the satellite altimeter data, topographical factors may also lead to inconsistency in the trend of the distribution of values during the interpolation process [32]. In two figures, there are significant differences between the marine…”
Section: Verification From Coastal Gravity Field Modelsmentioning
confidence: 99%
“…However, even for the same spatial resolution, varying interpolation methods make a significant difference in the accuracy of gridded marine gravity fields from the same data source [30]. Furthermore, when commonly used interpolation methods were compared, including inverse distance weighted (IDW), radial basis function (RBF), Shepard, and ordinary kriging, kriging has the highest accuracy but with an unacceptable accuracy loss in areas with sparse data density [31,32]. From the perspective of statistical analysis, adding data correlated with the predicted variables can improve the weight of the kriging predicted points [33].…”
Section: Introductionmentioning
confidence: 99%